PENURUNAN AKTIVITAS FAGOSITOSIS SEL MAKROFAG MENCIT SETELAH DISTIMULASI MINYAK ATSIRI KENCUR TERHADAP ACTINOBACILLUS ACTINOMYCETEMCOMITANS: REDUCING OF PHAGOCYTOSIS ACTIVITY OF MOUSE MACROPHAGE CELL AFTER STIMULATION KAEMPFERIA GALANGA LINNEUS TOWARDS ACTINOBACILLUS ACTINOMYCETEMCOMITANS - Tetiana Haniastuti (TALENTA, 2009)
Macrophage plays an essential role in innate immune system by phagocytosing bacteria. However, the phagocytosisprocess may activate macrophage to release inflammatory mediators which may cause tissue destructions in strongreaction. Kaempheria galanga L. is one of medical plants which is believed having potency as an immunomodulatoragent. The aim of this study was to examine macrophage cells phagocytic activity of Actinobacillus actinomycetemcomitans after stimulated with Kaempheria galanga`s essential oil in vitro. Mouse peritoneal macrophages wereincubated with 5%, 10%, and 20% of Kaempheria galanga`s essential oil at 37oC in an atmosphere containing 5% CO2.After 15 minutes, A. actinomycetemcomitans was added to the suspension and incubated for 30 minutes. At the end of theincubation period, the cells were assayed for the phagocytic activity. The result of this study showed that Kaempheriagalanga`s essential oil significantly reduced the percentage of mouse macrophage cells phagocytosing A. actinomycetemcomitans and the number of phagocytosed A. actinomycetemcomitans per 1 macrophage cell in vitro (p<0,05). Inconclusion, Kaempheria galanga`s essential oil may reduce mouse macrophage cells phagocytic activity of A.actinomycetemcomitans.